Engineering the System of Healthcare Delivery - Rouse, W.B. (IOS Press, 2013)
As the United States continues to debate reform of its healthcare system, this book argues that providing health insurance for all without improving the delivery system will not improve the current problems of access, affordability, and quality. The US healthcare system has many excellent components; strong scientific input, extraordinary technology for diagnosis and treatment, dedicated staff and top-class facilities among them. But the system has evolved haphazardly over time and although it has not failed entirely, the authors argue that like any system where attention is paid to individual components at the expense of the system as a whole, it can never hope to succeed. Above all, they point out that the US system does not provide high value healthcare; it has the highest costs in the world and yet many other countries have lower infant mortality rates and better life expectancy. Together with a team of highly regarded thought leaders, the authors of this publication advocate a complete re-thinking of healthcare from a systems perspective – an engineering approach to healthcare – and they then describe how to set about it. Covering a wide range of subjects including: health care costs and economics, barriers to change, integrated health systems, electronic records and computer-based patient support as well as patient safety and palliative and chronic care, this book will be of interest to all those involved in healthcare provision whose goal is affordable care to promote healthy, high quality lives.